2019
DOI: 10.2174/1389201020666190718164431
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of VEGF-C, VEGF-D, and VEGFR-3 in Different Grades of Endometrial Cancer

Abstract: Background: Vascular endothelial growth factor (VEGF)-C, -D, and VEGF receptor-3 are proteins characterized as crucial for tumor lymphangiogenesis. It is accompanied by angiogenesis during wound healing, but also in the neoplastic process. The research studies have shown that the lymphatic system plays a key role in the progression of carcinogenesis. Objective: The aim of this study was to evaluate changes in the expression of VEGF-C, VEGF-D and VEGFR-3 in different grades of endometrial cancer (G1-G3). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Evidence has been shown that VEGF correlated with angiogenesis and tumor growth in NHLs and HLs ( 46 , 47 ). VEGF family members have already known to stimulate angiogenesis and enable tumor neovascularization ( 48 , 49 ). Hoeres et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has been shown that VEGF correlated with angiogenesis and tumor growth in NHLs and HLs ( 46 , 47 ). VEGF family members have already known to stimulate angiogenesis and enable tumor neovascularization ( 48 , 49 ). Hoeres et al.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been shown that VEGF correlated with angiogenesis and tumor growth in NHLs and HLs (46,47). VEGF family members have already known to stimulate angiogenesis and enable tumor neovascularization (48,49). Hoeres et al found that lymphoma cell lines could produce VEGF, as well as release soluble VEGFR-1 simultaneously (50).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, TAM infiltration is closely associated with VEGF expression and microvascular density (MVD), which jointly affects the prognosis of patients [ 94 ]. In addition, previous studies have confirmed that VEGF-C, VEGF-D and their receptor VEGFR-3 were positively correlated with different stages of cervical lesions, allowing the development of lymphangion [ 95 , 96 ]. Interestingly, the expression of VEGF-C and VEGF-D increased significantly after the disease progressed to CIN3 stage [ 96 ].…”
Section: Introductionmentioning
confidence: 86%
“…Interestingly, the expression of VEGF-C and VEGF-D increased significantly after the disease progressed to CIN3 stage [ 96 ]. However, the opposite conclusion has been drawn in endometrial cancer [ 95 ]. One study reported that lower level of VEGF-C was detected in endometrial cancer samples [ 95 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, VEGFs regulate cell proliferation, invasion and migration during angiogenesis [64]. Signal transduction of VEGF-A occurs via VEGFR-1 and VEGFR-2, whilst VEGF-B and PlGF activate VEGFR-1 [65], and VEGF-C and VEGF-D show an affinity for VEGFR-3 (Figure 2) [66].…”
Section: Vascular Endothelial Growth Factors: Pivotal Angiogenesis Regulatorsmentioning
confidence: 99%